Kekuatan Akhlak dan Keikhlasan Terhadap Implementasi Kwalitas Keilmuan Penuntutnya - sabeni, ahmad; Sakdiah, Lailatul (FAKULTAS TARBIYAH, 2021)
In this journal, the author wants to convey several things about the strength of morals that can give someone the blessing of his knowledge, as well as the sincere power that encourages students of knowledge to reach knowledge that is blessed and useful. Among the changes that can be felt is in morality. Morals that can be interpreted are patterns of behavior that are generally found in society (Nasution, 1995: 63), in this era of globalization, there is an exchange of morality from one country to another. As a result of the exchange of morality resulted in positive and negative impacts. People who study without having sincerity and good morals, the student of knowledge lacks knowledge, while people who seek knowledge, which is based on sincerity and good morals, will have knowledge that is blessed and useful. The strength here is sincerity and good character. Through this journal, it is expected to be able to provide additional knowledge on the strength of morals and sincerity